2006
DOI: 10.7861/clinmedicine.6-3-281
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of in-hospital mortality and length of stay using an early warning scoring system: clinical audit

Abstract: -This aim of this study was to assess the impact of the introduction of a standardised early warning scoring system (SEWS) on physiological observations and patient outcomes in unselected acute admissions at point of entry to care. A sequential clinical audit was performed on 848 patients admitted to a combined medical and surgical assessment unit during two separate 11-day periods. Physiological parameters (respiratory rate, oxygen saturation, temperature, blood pressure, heart rate, and conscious level), in-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
144
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(149 citation statements)
references
References 11 publications
1
144
1
2
Order By: Relevance
“…16 For the other three outcomes, the AUROCs (95% CI) for the other 33 EWSs ranged from 0.570 (0.553 to 0.568) 17 to 0.827 (0.814 to 0.840) 18 (unanticipated ICU admission); 0.813 (0.802 to 0.824) 15 to 0.858 (0.849 to 0.867) 16 (death); and 0.736 (0.727 to 0.745) 17 to 0.834 (0.826 to 0.842) 19 (any outcome) ( Table 2). The comparative performance of each of the 33 EWSs and NEWS, for each of the four outcomes, is shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 For the other three outcomes, the AUROCs (95% CI) for the other 33 EWSs ranged from 0.570 (0.553 to 0.568) 17 to 0.827 (0.814 to 0.840) 18 (unanticipated ICU admission); 0.813 (0.802 to 0.824) 15 to 0.858 (0.849 to 0.867) 16 (death); and 0.736 (0.727 to 0.745) 17 to 0.834 (0.826 to 0.842) 19 (any outcome) ( Table 2). The comparative performance of each of the 33 EWSs and NEWS, for each of the four outcomes, is shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…The presentation of the efficiency curve for NEWS and the combined outcome ( Figure 3) provides a measure of the number of "triggers" that would be generated at different values of NEWS, thereby permitting hospitals to estimate the impact of choosing any particular NEWS value as the trigger for specific clinical intervention. Figure 4 demonstrates a significant reduction in the number of responses required to detect those who die, suffer a cardiac arrest or require unanticipated ICU admission within 24 hours of a given EWS value for NEWS compared to the EWS described by Paterson 19 -the best performing of the other 33 EWS evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that hospital mortality can be predicted on the basis of illness severity scores calculated at the time of admission, either in the emergency department, 18,19 an assessment unit 20,21 or a medical ward. 22 None of these studies looked at whether the average early warning scores varied according to time or day of admission; although such scores are somewhat blunt tools, this analysis may be a useful next step to help our understanding of the variation in mortality we have observed.…”
Section: Patient and Pre-hospital Factorsmentioning
confidence: 99%
“…The AWTTS allocates points to the vital parameters in a weighted manner. Since higher scores are associated with worse outcomes [51] , the use of an aggregated system may convince ward nurses and ward physicians to call for help if the score increases.…”
Section: Key Elements For Improvementmentioning
confidence: 99%